Pentingnya Pengaruh KepemimpinanTerhadap Kinerja Tim di Perusahaan PT Alfaria Trijaya Tbk - Danang Nugroho; Sinta Kusmawati; Rina Herlina; Rindi Tri Utami; Siska Dwi Syahidah; Siska Silvia Nurasyfa (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research discusses the influence of leadership on team performance at PT Sumber Alfaria Trijaya Tbk (Alfamart). This study is important because leadership is a key factor that determines an organization's success in achieving its goals. Alfamart, as a modern retail company with high business dynamics, requires a solid and high-performing team to face competition and achieve set targets.This research uses qualitative methods with descriptive analysis that relies on literature studies. The research results show that effective leadership has a significant impact on team performance, such as increasing motivation, collaboration, creativity, efficiency and customer service quality. Alfamart realizes the importance of effective leadership and implements various programs and training to develop the leadership abilities of its members. This is done through leadership training programs, performance appraisals, and a culture of appreciation.By implementing effective leadership and developing the leadership abilities of its members, Alfamart can continue to improve its team performance and achieve its business goals more effectively